Advancing community resilience research and practice: moving from "me" to "we" to "3D". Issue 1 (2nd January 2020) - Finucane, Melissa L.; Blum, Michael J.; Ramchand, Rajeev; Parker, Andrew M.; Nataraj, Shanthi; Clancy, Noreen; Cecchine, Gary; Chandra, Anita; Slack, Tim; Hobor, George; Ferreira, Regardt J.; Luu, Ky; et al.
Abstract: Research and practice aimed at enhancing community resilience to disasters such as hurricanes have focused primarily on the survival of individuals and the development of social capital and networks. Less consideration has been given to the dynamics of social-ecological conditions that can govern post-disaster outcomes. This article provides a rationale for moving research and practice towards an adaptive systems framework, drawing on the cascading challenges that Gulf of Mexico coastal communities have endured since the 2010 Deepwater Horizon (DWH) oil spill. The adaptive approach recognizes that, in some situations, crises can highlight avenues for improvement, where greater resilience can be achieved by addressing the dynamic context of a disaster. We discuss implications for clarifying interdependencies, bridging the science-society gap, and making course corrections through iterative processes. We also highlight how the approach might foster policy addressing global challenges such as changing climate conditions, rapid urbanization, and disease pandemics.